'Wiggle your Wits!' Social Restructuring and the Transformation of Entertainment Genres in Today's Russia. - Shevchenko, Olga (Social Identities, 2007)
Among print genres that soared in popularity after the fall of socialism, crossword puzzles have been prominent, with their monthly sales reported around 36 million copies in 2001-02. Drawing on ethnographic observation, interviews with crossword readers, traders and publishers, as well as on analysis of the puzzles themselves, I argue that the Russian crossword boom is an instructive case of how forms of popular entertainment are borrowed and re-appropriated to serve distinctively local cultural logics. More specifically, the recent popularity of crossword puzzles has to be viewed in the context of the sweeping changes in the social structure of the Russian society. In the face of multiple dislocations of postsocialism, of frustrated expectations and unfulfilled claims, the changed genre of crosswords, far less high-brow and encyclopaedic than its Soviet predecessor, offered a wide circle of Russians a vocabulary for articulating their claims of cultural competence and, increasingly, of moral worth, and allowed them to imagine themselves as a moral community juxtaposed to the hostility of the surrounding world.